PARTISIPASI KOMITE DALAM MENINGKATKAN MUTU SEKOLAH: STUDI ANALITIS KOMPARATIF DUA SEKOLAH DASAR DI KECAMARAN PARIGI - Jampi, Hironimus; -, Kaharuddin; Arifin, Jamaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The basic assumption of this study concerns the vagueness of the existence of school committees, therefore, their participation is still being debated. This comparative case study explicitly adopts a qualitative method in which the investigation is directed at the Forms and differential aspects of the participation of two committees, namely Pattallassang and Batumenteng, which are modeled through the features of Nvivo 12 Plus. The study involved 10 respondents to obtain an overview of the specific and general aspects of the two committees, and data were collected using interview and observation techniques. The results of the analysis show that there are four forms of participation between the two committees, namely: a) Ensuring the Quality of Education Services; b) Social Service; c) School Management, and; d) Providing Assistance. While the differences in participation between the two are influenced by two general categories with specific sub-indicators, namely: 1) Knowledge Factor, and; 2) Motivation Factor or Participation Mode.